(untitled) (Texas Journal of Engineering and Technology, 2024)
The mechanism of rock destruction by explosion is generally characterized by the short duration of the application of the load to the destroyed volume of the medium and depends on many factors. Therefore, to date there is no generally accepted theory about the mechanism of rock destruction. Generalization of the existing hypotheses about the physical nature of the explosion action in a solid medium makes it possible to improve the control of the explosion action.